Labour Underutilisation in Metropolitan Labour Markets in Australia: Individual Characteristics, Personal Circumstances and Local Labour Markets - Mitchell, W; Bill, A; Baum, S (My University, 2008)
There has been a growing awareness that the issue of labour market disadvantage is substantially greater than merely considering unemployment and the ability to find a job. There is an increasing literature that points to the advantages of considering a broader concept which accounts not only for those people who are traditionally unemployed, but also for individuals who are underemployed and those who are sub-unemployed or discouraged workers. Taking multidimensional survey and census data for Australian metropolitan regions, this paper applies a broad employability framework to an understanding of labour underutilisation which presents the risk of underutilisation as a function of individual characteristics, personal circumstances and the impact of local labour market characteristics. The analysis finds that the risk of labour underutilisation is associated with a range of individual characteristics and personal circumstances together with the characteristics of the metropolitan local labour market.
Urban Studies
Keywords: Location -- Metropolitan/urban; Location; Employment; Housing, communities and neighbourhoods; Labour market; Employment; Location; Metropolitan/urban; Housing, communities and neighbourhoods; Employment and unemployment